Factors of Youth’s Internet Addiction Development - Kaminska, Olga (Psychological Prospects Journal, 2015)
The article analyzes the specifics of the emergence of Internet addiction based on various factors that influence this process. It determines the relevance of Internet addiction because of its rapid spread, especially among youth. It analyzes the recent gains of studying this problem. It provides studying the relationship of Internet addiction based on place of residence and level of education of the individual. It defines the basic psychological mechanisms that affect the occurrence and development of addiction. The degree of addiction based on whether respondents live in regional centers, cities of regional subordination, towns or villages. The scale of Internet addiction (Chen), the author’s technique of studying Internet addiction using incomplete sentences, methods of observation and conversation were used during the research. A method of mathematic statistics such as a criterion of consistency Pearson was used to confirm the significance of detected differences. Analysis of the data at different scales of these techniques has allowed to carry out diverse study the characteristics of the formation and manifestation of Internet addiction and psychological mechanisms that influence the development of addiction. When analyzing the prevalence of Internet addiction based on residence investigated it was found that the greatest extent it is common among people living in regional centers, and the least common – among villagers. The article proves social and psychological patterns that are the basis of the detected patterns. It determines that this trend is due to the specific construction of interpersonal relationships in cities and villages. Thus, between the villagers there is less psycho- logical distance because usually people in the villages know each other, between them there is a system of relations. Identifying the impact of education on the individual process of Internet addiction found that more addiction equip individuals with incomplete secondary education, and to a lesser extent – with higher. It determines the basic psychological mechanisms that influence the development of addiction.